Characterization of hypomineralization second primary molar and molar incisor hypomineralization in patients with orofacial clefts - de Farias, Aline Leite [UNESP]; Rojas-Gualdrón, Diego Fernando; Restrepo, Manuel; Zecchin, Karina Gottardello; Bussaneli, Diego Girotto [UNESP]; Yupanqui, Kasandra [UNESP]; Raposo‑Amaral, Cassio Eduardo; Santos-Pinto, Lourdes [UNESP] (Springer Nature, 2025)
AimsTo identify and characterize hypomineralization in the second primary molar (HSPM) and molar incisor hypomineralization (MIH), as well as other developmental defects of enamel (DDE) in patients with clefts considering dentition type, tooth type, phenotype and cleft laterality.Materials and methodsIn this cross-sectional retrospective study, 6432 deciduous and permanent teeth of 290 patients with clefts aged between 3 and 14 years in a referral hospital were assessed using intraoral photographs. The classification of demarcated hypomineralization was carried out by a calibrated examiner using the MIH index. Statistical analyses were performed using a binomial generalized linear model.ResultsDeciduous and permanent molars were the most affected by HSPM and MIH, whereas incisors and canines were most affected by hypoplasia, with the upper arch being most affected by DDE. Cleft phenotypes involving the palate were associated with HSPM (OR = 31; 95% CI: 1.0–59.3) and MIH (OR = 31.6; 95% CI: 0.6–53.2).ConclusionPatients with clefts had a high prevalence of HSPM and MIH in the upper arch and were associated with more severe cleft phenotypes.Clinical relevancePediatric dentists who are members of the multidisciplinary teams responsible for caring for patients with clefts need to have a more discerning clinical eye when diagnosing DDE in patients with clefts. Posterior teeth are more susceptible to demarcated hypomineralizations in patients with clefts, while anterior teeth are more susceptible to hypoplasias.